Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Andika Rajawali Indoserpis Depok - Agusria Boru Sibagariang; Rosento Rosento (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
PT Andika Rajawali Indoserpis is a company that operates in the field of security/security services and providing labor. The aim of this research is to determine the partial and simultaneous influence of work motivation and work discipline on employee performance. The number of samples in this study was 60 people using the Survey method. Next, the data collection technique used was the distribution of questionnaires using a rating scale model. The data analysis technique used is multiple linear regression. Based on partial research results, work motivation has a positive relationship with employee performance. Providing motivation from the company will encourage employees to complete their work well and have an impact on increased performance. Apart from work motivation, work discipline has an influence on employee performance. The existence of high work discipline possessed by employees will influence the resulting performance. Simultaneously, work motivation and work discipline have an influence on the resulting employee performance. Through the research results of the coefficient of determination test, the R Square value of 0.651 shows that the variables of work motivation and work discipline have a 65.1% influence on employee performance at PT Andika Rajawali Indoserpis. And the remaining 34.9% is influenced by other factors such as leadership and work environment.